PERANCANGAN PURWARUPA DASHBOARD DIGITAL UNTUK PENGUKURAN PRODUKTIVITAS KERJA DENGAN METODE DESIGN THINIKING - Firly Wiryandhani; Suprih Widodo; Rian Andrian (Universitas Teknokrat Indonesia, 2023)
Employee productivity is one of the important factors in the progress of the company, to measure productivity time and motion methods are used and a dashboard is needed to review the level of employee productivity. Making dashboards manually takes a long time, while stakeholders need progressive and fast information. So a digital dashboard prototype design was made to meet user needs, then a research method focused on user needs, namely Design Thinking. The stages of this method are empathize, define, ideate, prototype, and test. The implementation of this method begins with interviewing potential users with questions that can explore user needs and direct observation, the answers of potential users will be analyzed so that they are properly defined, and problems that are defined will be given solution ideas that meet user needs, solution ideas will be applied as a digital dashboard prototype design and will be tested to test the prototype using usability testing to determine the effectiveness and efficiency of the prototype made. From the steps carried out to produce conclusions such as defined problems, solution ideas are obtained that are applied to the prototype, with the previously designed image making it easier to work on the prototype design and the test results proving that the prototype that has been designed is effective and efficient, the level of completion of the task carried out. the tester got a perfect score with a 100% success rate and a relatively fast task completion speed.